Effectiveness of Cognitive Behavior Therapy on the Quality of Sleep in Elderly People With Insomnia Disorder - Reza Mottaghi (Sālmand, 2016)
Objectives: Taking into consideration the high prevalence of insomnia disorder in the elderly population, this study aims to examine the effectiveness of cognitive behavioral therapy (CBT) in improving the overall quality of sleep and the subscales of sleep quality in the elderly.